A vida de um povo em territórios estranhos: - SILVA, Railton Santos da. (Universidade Federal do Tocantins, 2024)
This work presents the migratory dynamics carried out by Venezuelan refugees in the city of Araguaína - TO. Venezuelan refugees left Venezuela, fleeing the political crisis and civil war, abandoning a whole history and singularities. The objective of this research is to understand the reasons that led these immigrants to come to Brazil, especially to the city of Araguaína as the case of Venezuelans, in their magnitude motivated by political, economic and social issues in their country of origin, as well as the welfare policies of the municipality in relation to refugee families. The methodology adopted was based on exploratory research involving bibliographical survey and interviews, qualitative because the way of life of refugees was investigated, explanatory because it sought to identify the factors that determine the research problem. Among the results, the reception and incentive policies for the immigrant's autonomy can be highlighted.